Decommissioning Asset Management System for Fixed Steel Jacket - MOHD FUAD, NORFATIN NAJWA (Universiti Teknologi PETRONAS, 2017)
Malaysia has approximately 362 offshore platforms and most of these platform has exceeded the design life and thus leading to decommissioning study for dismantling the offshore structures. Several decommissioning alternatives are listed which include total removal and partial removal for reuse, onshore disposal, artificial reefs and topple in-situ. In addition, Malaysian waters are classified into four region namely, Peninsular Malaysia Asset (PMA), Sabah Asset (SBA), Sarawak Gas (SKG) and Sarawak Operation (SKO). In this study, design and characteristic data for fixed offshore platforms in SKO were collected and kept as a database. Hence, platforms selection can be identified for decommissioning and study the cost of previous successful decommissioning project. In summary, the main goal for this study aims to develop an asset management system for decommissioning strategy to reduce overall decommissioning cost and explore potential alternative such as reefing.